Ocular Biometry, Optic Nerve Head Parameters And Retinal Nerve Fiber Layer Thickness In Severe Preterm Malay Children - Salem, Alshaarawi M.A. (2012)
Introduction: Severe preterm delivery is defined as babies born at 32 weeks or less of gestation. The earlier the baby is born, the less likely he or she is to survive. Those who do survive are at a higher risk of lifelong health problems, of which the ophthalmic complications include retinopathy of prematurity, myopia, amblyobia, strabismus and optic nerve abnormalities. Objective : This study is to compare the ocular biometric parameters, optic nerve head parameters, and retinal nerve fiber layer thickness parameters between severe preterm and term Malay children aged 8-16 years old. Methodology: This comparison cross sectional study evaluated 64 patients, 32 patients were born less than 32 weeks of gestation and 32 patients were full term. All patients underwent thorough eye examination. Ocular biometry was performed using A- Scan ultrasound biometry, whilst optic nerve head parameters and retinal nerve fiber layer thickness were performed using Heidelberg Retinal Tomograph III.